Thioridazine: a potential adjuvant in pharmacotherapy of drug resistant tuberculosis Ki - Kishore, Kiran K.; Ramakanth, G. S. H.; Chandrasekhar, N.; Kishan, P. V.; Chiranjeevi, Uday Kumar; Usharani, P. (International Journal of Basic & Clinical Pharmacology, 2017)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Despite advances in control strategies, inadequate treatment and failure to comply with drug regimens have resulted in TB to emerge as one of the most common and deadly infectious diseases worldwide. The emergence of drug-resistant TBhas evolved as a formidable obstacle for comprehensive TB control. Drug-resistant TB can be classified as multi-drug-resistant TB, extensively drug-resistant TB and totally drug resistant TB (TDR-TB). There is a paucity in the development of new drugs against drug-resistant mycobacteria. The focus has shifted to the exploration of anti-mycobacterial properties of drugs approved for other indications. Thioridazine, a drug approved for use in schizophrenia is one such potential agent, which has shown anti-mycobacterial activity. There is evidence of anti-mycobacterial action of Thioridazine in in-vitro and mouse models. There is a compelling need for new anti-mycobacterial drugs that are more effective and have less toxicity. Further clinical trials are advocated favoring the use of thioridazine as an adjuvant in the treatment of TB, especially TDR-TB.